Odpowiedzi

2010-02-21T15:17:26+01:00
A)
4x-3y= -1|*2
5x+2y=4,5|*3

8x-6y=-2
15x+6y=13,5
23x=11,5
x=0,5

4*0,5-3y=-1
-3y=-1-2
-3y=-3
y=1


b)
3x+2y=23|*3
4x+3y= -9|*(-2)

9x+6y=69
-8x-6y=18
x=87

3*87+2y=23
2y=23-261
2y=-238
y=-119


c)
5x-7y=3|*3
2x-3y=7|*(-7)

15x-21y=9
-14x+21y=-49
x=-40

5*(-40)-7y=3
-7y=3+200
-7y=203
y=-29


d)
4x-5y=5|*3
6x-7y=9|*(-2)

12x-15y=15
-12x+14y=-18
-y=-3
y=3

4x-5*3=5
4x=5+15
4x=20
x=5


e)
2x+3y+18=0
3x+5y+29=0

2x+3y=-18|*3
3x+5y=-29|*(-2)

6x+9y=-54
-6x-10y=58
-y=4
y=-4

2x+3*(-4)=-18
2x=-18+12
2x=-6
x=-3


f)
3x+2y=6,3|*2
2x+5y=8,6|*(-3)

6x+4y=12,6
-6x-15y=-25,8
-11y=-13,2
y=1,2

3x+2*1,2=6,3
3x=6,3-2,4
3x=3,9
x=1,3